Photochemical Probe Identification of a Small‐Molecule Inhibitor Binding Site in Hedgehog Acyltransferase (HHAT). Issue 24 (14th May 2021) - Lanyon‐Hogg, Thomas; Ritzefeld, Markus; Zhang, Leran; Andrei, Sebastian A.; Pogranyi, Balazs; Mondal, Milon; Sefer, Lea; Johnston, Callum D.; Coupland, Claire E.; Greenfield, Jake L.; Newington, Joshua; Fuchter, Matthew J.; et al.
Abstract: The mammalian membrane‐bound O ‐acyltransferase (MBOAT) superfamily is involved in biological processes including growth, development and appetite sensing. MBOATs are attractive drug targets in cancer and obesity; however, information on the binding site and molecular mechanisms underlying small‐molecule inhibition is elusive. This study reports rational development of a photochemical probe to interrogate a novel small‐molecule inhibitor binding site in the human MBOAT Hedgehog acyltransferase (HHAT). Structure‐activity relationship investigation identified single enantiomer IMP‐1575, the most potent HHAT inhibitor reported to‐date, and guided design of photocrosslinking probes that maintained HHAT‐inhibitory potency. Photocrosslinking and proteomic sequencing of HHAT delivered identification of the first small‐molecule binding site in a mammalian MBOAT. Topology and homology data suggested a potential mechanism for HHAT inhibition which was confirmed by kinetic analysis. Our results provide an optimal HHAT tool inhibitor IMP‐1575 ( K i =38 nM) and a strategy for mapping small molecule interaction sites in MBOATs. Abstract : Structure‐activity relationship analysis of Hedgehog acyltransferase (HHAT) inhibitors allowed rational design of photochemical probes for HHAT. Probe photocrosslinking identified the first small‐molecule inhibitor binding site in HHAT and revealed the inhibitory mechanism, providing an optimal HHAT tool inhibitor IMP‐1575 ( K i =38 nM) for future studies.